Deterioration of Soybean [Glycine Max (L.) Merr.] Seed by Colletotrichum Truncatum and its Control Through Bio-priming - Begum, Most. Mahbuba (2008)
A study was conducted to evaluate the effect of Colletotrichum truncatum infection on soybean seed quality and its control through bio-priming. A total of 11 genera comprising of 17 species of seed-borne fungi were found to be associated with soybean var. Palmetto. The prominent fungus isolated externally and internally was C. truncatum with the frequency values of 12.75 and 9.75%, respectively, followed by Fusarium oxysporum f. sp. glycines and Diaporthe phaseolorum var. sojae based on moist blotter and agar plate methods. The typical symptoms of C. truncatum on the infected seeds appeared as brown to black speckled lesions, producing numerous acervuli with black setae and conidia over the seed surface. Seed infection by C. truncatum in soybean seed caused pre and post-emergence damping-off, resulting in reduced seed germination and seedling survivability by 62.35 and 88.24%, respectively. Histopathological studies of naturally infected soybean seeds confirmed the presence of C. truncatum predominantly both intra- and inter-cellularly in the seed coat, cotyledon and embryonic axes of seed. The fungi were also detected on and in the seed coat, cotyledon and embryonic axes of artificially infected seeds. Seed viability and vigour were also reduced in C. truncatum infected seeds as determined by tetrazolium (TZ) and electrical conductivity (EC) tests. Seed volume of infected seeds was reduced, with an increase in soluble protein and oleic acid and a decrease in linoleic acid content as compared with healthy seeds. Two fungal biocontrol agents (BCAs), Trichoderma virens (UPM23) and T. harzianum (UPM40) were found to inhibit strongly the growth of C. truncatum through mycoparasitism, competition and antibiosis based on PIRG (Percent Inhibition of Radial Growth) values. However, one bacterial BCA, Pseudomonas aeruginosa (UPM13B8) gave the highest PIRG values of 100% in the culture filtrate test, suggesting that antibiosis could be the main mechanism of antagonism. No phytotoxic effect was observed on soybean seeds and seedlings, when treated with suspensions of UPM23, UPM40 and UPM13B8. Therefore, the efficacy of bio-priming was conducted for controlling C. truncatum infection in soybean seeds using UPM23, UPM40 and UPM13B8. Artificially infected seeds by C. truncatum were bio-primed for 12 hours as this was determined as the safe time limit for soybean. Treatments included were chemo-primed, Benlate® (T1); bio-primed, UPM13B8 (T2); bio-primed, UPM40 (T3); bio-primed, UPM23 (T4); bio-primed, UPM23+40 (T5) and the controls as hydro- primed (T6) and non- primed seeds (T7). Trichoderma isolates used either singly (UPM 23 and UPM40) or as a mixture (UPM23+40) colonized the seed surface with germinating hyphae after 12 hours of bio-priming. Bacterial isolate, P. aeruginosa was also detected to colonize the seed surface with increase in the colony forming unit (CFU) from 1.2 × 109 to 5.1 × 109 seed-1 after the bio-priming period. Bio-priming was effective to control pre and post-emergence damping-off and promote seed germination, seedling establishment and growth in the presence of C. truncatum in soybean seeds. Under the glass house conditions, Trichoderma isolates however, gave better control of pre and post-emergence damping-off and enhancement of growth followed by bio-priming with UPM13B8 and chemo-priming with Benlate®. Under the field conditions, UPM13B8 was better in controlling pre and post-emergence damping-off ranging from 48.64 to 51.85% and 65.0 to 97.20%, respectively and also enhanced seed germination, final seedling stand and increase in shoot length and dry weight of seedling. However, the biocontrol efficacy and subsequent growth enhancement of UPM13B8 were not significantly (P≤0.05) different from UPM40 or UPM23+40 or the fungicide ‘Benlate®’. Bio-priming with Malaysian isolates of P. aeruginosa and T. harzianum offered an effective biological seed treatment system and an alternative to chemo-priming with Benlate® to control seed-borne infection by C. truncatum in seeds and seedlings of soybean. Besides, they also improve seed germination, seedling establishment and vegetative growth. This study has explored up new dimension of biological control for preventive as well as remedial of seed-borne infection by C. truncatum. Thus, bio-priming can be exploited by seed companies and organic farmers in the sustainable agriculture, which would be more economical and environmental friendly.